Handling does not affect reproductive signals of male threespine stickleback - Laurin, André Y; Scott, Robert J (Environmental biology of fishes, 2009)
We examined the affect of handling on reproductive signal expression in male threespine stickleback, Gasterosteus aculeatus. Spectrophotometric techniques have become popular methods for measuring fish color, but the measurements require handling of the subjects in order to make measurements. Fish can undergo rapid physiological color change in response to stress. As such, handling fish may induce color changes and measured colour may not be representative of signal appearance under non-stressful conditions. We measured the reflectance characteristics of the opercular, ventro-lateral and dorso-lateral areas of 41 reproductive males from Hotel Lake, BC, Canada using spectroradiometry immediately upon capture and again at 2, 3, 4, 5, 10, 15, and 20 min post-capture. Repeated measures ANOVA revealed that post-capture handling did not affect opercular or ventro-lateral reflectance characteristics over the 20 min period. However, we did observe a change in dorso-lateral reflectance characteristics of parental males over the experiment. The results of our study show that handling does not influence reflective properties of two key components of stickleback reproductive signals during a time frame that is reasonable for taking field measurements of signal color.